Real-time estimation of blood oxygenation parameters from human foot sole during leg elevation: a preliminary study with diffuse reflectance spectroscopy - Kumar, Ajay; Lohchab, Viney; Pawar, Dnyandeo; Someshwar, Vimal; Mathe, Vikas; Husale, Sudhir; Kanawade, Rajesh (Optics and Laser Technology, 2025)
This study investigated the applicability of diffuse reflectance spectroscopy (DRS) for real-time and non-invasive measurement of blood oxygenation parameters (BOPs) such as reduced hemoglobin (RHb), oxyhemoglobin (HbO(2)), and oxygen saturation (SO2) from human foot sole during leg elevation. Seventeen (17) healthy male subjects aged between 21 to 39 years were included in this study. Diffuse reflectance spectra were recorded from measurement sites namely the 5th metatarsal, ball of great joint, calcaneum, and great toe of the human foot sole w.r.t. leg elevation angles such as 0(0), 15(0), 30(0), 45(0), and 60(0), respectively. The localized BOPs were derived from the recorded spectra. In addition, blood hemodynamic parameters (BHPs) such as heart rate (HR), SO2, perfusion index (PI), systolic blood pressure (SBP), and diastolic blood pressure (DBP) were also measured for each elevating angle. To study and assess the changes in BOPs and BHPs w.r.t. leg elevation, a One-way ANOVA test followed by a Tukey HSD post-hoc test was performed. We observed a statistically significant increase in RHb (p < 0.001) and a decrease in HbO(2) (p < 0.001) after 45 degrees of leg elevation, however, there was no statistically significant difference in SO2 (p = 0.74) and HR (p = 0.84) for each measurement site w.r.t. leg elevation, respectively. Furthermore, PI (p < 0.01), ankle SBP (p < 0.001) and DBP (p < 0.001) were decreased w.r.t. leg elevation. The obtained results are in agreement with the literature. The preliminary results suggest that DRS has the potential for real-time estimation of BOPs from the local sites of healthy human foot soles during leg elevation. Thus, it opens the possibility of DRS to monitor and evaluate the diagnosis and treatment of ischemia and edema during leg elevation of patients through BOPs measurement.
Keywords: diabetic foot ulcer; diffuse reflectance spectroscopy; Leg elevation; Oxygen saturation; Oxyhemoglobin; Reduced hemoglobin